Theoretical and unused potential for residual biomasses in the Emilia Romagna Region (Italy) through a revised and portable framework for their categorization. (September 2019) - Greggio, Nicolas; Balugani, Enrico; Carlini, Carlotta; Contin, Andrea; Labartino, Nicola; Porcelli, Roberto; Quaranta, Marta; Righi, Serena; Vogli, Luciano; Marazza, Diego
Abstract: Global energy demand is lowering its growth, but it is still expected to increase by 30% between now and 2040. To decrease greenhouse gas emissions a shift to more sustainable renewable energy sources is fundamental. Among the renewable energy sources, biomasses already have the largest share in Europe and their future demand for biorefinery plants will increase at global level. This study provides a comprehensive and exportable categorization of the residual biomasses (RB) from different supply sectors. Thanks to the individual descriptive and quantitative parameters introduced in the paper, an estimate of the theoretical and techno-economic potential is presented for a well-industrialized, agricultural-oriented and environmentally advanced European Region. Results are presented as recoverable biogas or biomethane, considering also the seasonal availability. In a relatively small region like Emilia Romagna (Italy), 106 different types of residual biomasses belonging to 6 main groups have been characterized. Over half of the total residues come from the agro-industrial and food businesses (58) followed by the agricultural sector (33). The estimate reveals a theoretical potential of 3544 ± 291 Gg/year of total solids for thermochemical valorisation and 3460 ± 639 Gg/year of total solids suitable for biological treatment. In terms of unused potential, the quantities decrease respectively to 2120 ± 298 and 915 ± 167 Gg/year. The estimates indicate stable results over the years from 2014 to 2016. The seasonal availability shows two evident peaks from August to October, while a significant shortage is present from April to June for the residues suitable for thermochemical valorisation. The theoretical potential that can be obtained from the Region's residues corresponds to about 1.8–2.3 million TOE/year, corresponding to 13–17% of the total regional consumption. Unused residues contribute to 0.9–1.2 million TOE/year. Graphical abstract: Image 1 Highlights: A fully comprehensive and exportable categorization of the RBs is developed. 106 residual biomasses have been identified and estimated in Emilia Romagna Region. About 1.5 Mg/year/capita of total solids is produced in the Region. The theoretical RB potential covers the 13–17% of the regional energy consumption. The unused RB potential decrease to 7–9% of the annual regional energy consumption.